Design and fabrication of a low-cost wireless camera imaging system for centrifugal microfluidics - Brian Regan (18418860) (2022)
Centrifugal microfluidic devices offer a robust method for low-volume fluid handling by combining low-cost instrumentation with highly integrated automation. Crucial to the efficacy of Lab-on-a-Disc (LoaD) device operation is the selection of robust valving technology, the design of on-disc fluidic structures, and accurate control of disc spin-speeds (centrifugal force) during operation. The design and refinement of fluidic and valving structures is often guided by inspecting disc operation using high-speed camera systems. This approach involves synchronising image acquisition with disc rotation to visualise liquid flow through a series of images often presented in a video format. Depending on the decisions taken, such systems can cost from €4,000 upwards. This paper outlines the development of a low-cost centrifugal test-stand with an integrated imaging system using a generic wireless camera to record videos directly to a smartphone device. This imaging system can be fabricated using only 3D printers and a low-cost CNC milling machine from widely available materials for approximately €350. High-fidelity imaging of the entire disc for flow visualisation and the recording of real-time colour intensity measurements are facilitated by this standalone device. A vibration analysis study has been performed to determine the rotational velocity range at which the system can be safely operated. Furthermore, the efficacy of the imaging system has been demonstrated by performing real-time colour intensity measurements of dyed water dilutions. Other Information Published in: HardwareX License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ohx.2022.e00259